MORFOLOGI BUNGA YANG SESUAI BAGI KULTUR MIKROSPORA PADA TANAMAN JARAK PAGAR (Jatropha curcas L.) - Suaib, Suaib; Arma, Makmur Jaya; Muhidin, Muhidin (Jurnal Agroteknos, 2014)
An experiment aimed in gaining information on morphological characteristics of Jatropha curcas (L.) containing high frequency of uninucleate microspores has been done. This was important due to the successful application of experiment in haploid technique through anther or microspore culture is strongly determined by the availability of information from basic research such as appropriate morphology of the flowers. This scientific article, in our knowledge, was an early explanation of the initial steps of whole procedures in the microspore culture of Jatropha curcas (L.).  Results of the research showed that the morphological features of flower that contained high frequency of mid- and late uninucleate microspores was that the flowers must be in the range of 2 to 3 mm in length. Such flowers contained yellowish anthers.Key words: Flowers length, mid- and late-uninucleate, morphology, physic nut, microspore